Zeros of Solutions and Their Derivatives of Higher Order Non-homogeneous Linear Differential Equations - Belaïdi; Latreuch, Zinelâabidine (Communications in Mathematics, 2015)
This paper is devoted to studying the growth and oscillation of solutions and their derivatives of higher order non-homogeneous linear di erential equations with nite order meromorphic coe cients. Illustrative examples are also treated.
Keywords: Linear differential equations; meromorphic functions; Exponent of convergence of the sequence of zeros